PET Evidence for a Role for Striatal Dopamine in the Attentional Blink: Functional Implications - Slagter, Heleen A.; Tomer, Rachel; Christian, Bradley T.; Fox, Andrew S.; Colzato, Lorenza S.; King, Carlye R.; Murali, Dhanabalan; Davidson, Richard J. (Journal of cognitive neuroscience, 2012)
Our outside world changes continuously, for example, when driving through traffic. An important question is how our brain deals with this constant barrage of rapidly changing sensory input and flexibly selects only newly goal-relevant information for further capacity-limited processing in working memory. The challenge our brain faces is experimentally captured by the attentional blink (AB): an impairment in detecting the second of two target stimuli presented in close temporal proximity among distracters. Many theories have been proposed to explain this deficit in processing goal-relevant information, with some attributing the AB to capacity limitations related to encoding of the first target and others assigning a critical role to on-line selection mechanisms that control access to working memory. The current study examined the role of striatal dopamine in the AB, given its known role in regulating the contents of working memory. Specifically, participants performed an AB task and their basal level of dopamine D2-like receptor binding was measured using PET and [F-18]fallypride. As predicted, individual differences analyses showed that greater D2-like receptor binding in the striatum was associated with a larger AB, implicating striatal dopamine and mechanisms that control access to working memory in the AB. Specifically, we propose that striatal dopamine may determine the AB by regulating the threshold for working memory updating, providing a testable physiological basis for this deficit in gating rapidly changing visual information. A challenge for current models of the AB lies in connecting more directly to these neurobiological data.